Enhancing Iota Carrageenan Soft Capsules with Modified Starch - Perwatasari, Dayu Dian; Putri, Renny Primasari Gustia; Puspantari, Widya; Royanti, Ida; Wibowo, Des Saputro; Hidayat, Taufik; Wahyuni, Tuti; Purwoto, Heri; Manalu, Lamhot Parulian; Laksono, Hendrawan (Science and Technology Indonesia, 2025)
Due to the increasing demand for gelatin alternatives, iota carrageenan, a polymer derived from seaweed, is being explored as a potential base material for soft capsule production. However, the rheological properties of iota carrageenan alone are insufficient for commercial manufacturing, necessitating the addition of fillers such as modified starches. This study evaluates the performance of iota carrageenan-based soft capsule shells using modified cassava, potato, and sago starches as fillers. Various mechanical and rheological properties were assessed, including elongation, stickiness, tensile strength, and viscosity. The results demonstrated that modified cassava starch provided the best overall balance of mechanical properties, exhibiting superior moldability (47.56 mm elongation), flexibility, and moderate stickiness (567.45 gf). Scanning Electron Microscopy (SEM) analysis revealed that cassava starch capsules had a more uniform outer surface with smoother internal morphology than other starches. These findings suggest that modified cassava starch is a promising candidate for large-scale production of high-quality soft capsules.